Changes in muscle architecture of vastus lateralis muscle after an alpine snowboarding race - Vernillo, G.; Pisoni, C.; Sconfienza, L. M.; Thiébat, G.; Longo, S. (The Journal of Strength and Conditioning Research, 2017)
This study aimed to assess acute changes of vastus lateralis (VL) muscle architecture after an alpine snowboarding simulated race and to compare architecture characteristics between the front and rear legs on elite alpine snowboarders. Using ultrasonography, VL muscle thickness (MT), pennation angles (o), and fascicle lengths (Lf) were assessed in 8 elite alpine snowboarders (25.6 ± 4.4 years; stature: 178.4 ± 9.8 cm; body mass: 78.1 ± 12.1 kg) before and directly after an alpine snowboarding simulated race under competition rules. Muscle thickness, o, and Lf showed no meaningful changes (P > 0.05, differences reported as trivial) after the race for both legs. The rear leg tended to have a 14.0% lower o (P = 0.04, differences rated as moderate) and a 13.6% higher Lf (P = 0.04, differences rated as moderate) compared with the front leg. Changes in muscle architecture are not observable immediately after an alpine snowboarding simulated race. The ~14.0% difference in muscle architecture between the front and the rear leg suggests the presence of a morphological asymmetry in elite alpine snowboarders with direct implications for injury prevention and training prescription.